Badan Usaha Milik Desa (BUMDes) Binangun Pagerharjo sebagai Penggerak Ekonomi Desa dalam Peningkatan Pendapatan Asli Desa (PADes) - Putriana Nurani; Nuralam Nuralam; Andriya Risdwiyanto (Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Activity (PkM) aims to improve the management system of the Binangun Pagerharjo Village-Owned Enterprise (BUMDes) in Pagerharjo Village, Samigaluh, Kulon Progo as well as an effort to increase Village Original Income (PADes). This activity includes training and mentoring that emphasizes the importance of understanding the needs and challenges faced by BUMDes and the surrounding community, The results of the PkM carried out show that the management of BUMDes Binangun Pagerharjo is still simple but has plans for future improvements. BUMDes can be an example for other BUMdes. In terms of innovation and development, BUMDes can be a source of village income. The management and strategies offered as a result of PkM are more about BUMDes management, namely operational systems and marketing digitalization, to strengthen the management system for BUMDes Binangun Pagerharjo.